Genotypes×Environment Interaction of Faba bean (Vicia faba L.) Genotypes Using AMMI Model in Arsi Zone, Southeastern Ethiopia - Yilma, Gizachew; Yimam, Kedir; Achenef, Gebeyaw (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during 2016 and 2017 main cropping season (August–December) at Kulumsa, Bekoji and Kofele in southeastern Ethiopia to select the most promising faba bean genotypes across different environmental conditions in the southeastern Ethiopia. Thirteen faba bean genotype were evaluated by RCBD using four replications. From the combined mean performance none of the candidate genotypes showed better yield performance than the standard check Gora and Tumsa. The AMMI analysis of variance for grain yield showed a significant difference among environments and genotype by environment (p<0.05). Non-significant variation were observed among genotypes. The environmental effect accounted for 50% of the total variation, whereas the genotype by environment and genotype effect accounted about 4 and 6% respectively. Higher mean grain yield was recorded from environment 6 (4,754.6 kg ha-1) followed by environment 2 (4,563 kg ha-1) and 1 (4,236.2 kg ha-1). The first IPCA1 captured about 30.9% of genotype×environmental interactions sum square, while the second IPCA1 explained about 26.4%. The two IPC cumulatively explained 57.3%. G6, G8, G9, G11 and G5 have the lower ASV value and these were the most stable genotypes. Using AMMI bi-plot analysis E3, E4 and E5 are unfavorable environments while E1, E2 and E6 were favorable environments. The results showed the promising genotypes for future release of well adapted faba bean varieties in the growing areas of Ethiopia.